2011
DOI: 10.1089/end.2009.0676
|View full text |Cite
|
Sign up to set email alerts
|

Pure Natural Orifice Translumenal Endoscopic Surgery Management of Simple Renal Cysts: 2-Year Follow-Up Results

Abstract: Retrograde ureteroscopic marsupialization is a complete transurethral NOTES marsupialization. With appropriate patient selection, the minimally invasive retrograde ureteroscopic marsupialization is feasible, safe, and effective. It can be preferred to more invasive laparoscopic or open surgical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The key to the incision and drainage of parapelvic renal cysts via flexible ureteroscopy is the accurate location of the cysts. The present study suggested that the evaluation of cyst positioning should include ultrasonography, intravenous urography, retrograde pyelography, CT and an enhanced CT (2,(14)(15)(16)(17)(18)(19)(20). A recent Chinese randomized controlled trial confirmed that the injection of methylene blue into the parapelvic renal cysts reduced the identification time and operation time of the cysts under a flexible ureteroscope (21).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The key to the incision and drainage of parapelvic renal cysts via flexible ureteroscopy is the accurate location of the cysts. The present study suggested that the evaluation of cyst positioning should include ultrasonography, intravenous urography, retrograde pyelography, CT and an enhanced CT (2,(14)(15)(16)(17)(18)(19)(20). A recent Chinese randomized controlled trial confirmed that the injection of methylene blue into the parapelvic renal cysts reduced the identification time and operation time of the cysts under a flexible ureteroscope (21).…”
Section: Discussionmentioning
confidence: 67%
“…The surgical path of flexible ureteroscopic surgery runs closer to parapelvic renal cysts than the laparoscopic surgery anatomically (14). As this technique is transluminal naturally and leads to less bleeding, less risk and faster recovery, it has been favoured by a considerable number of urologists (2,(14)(15)(16)(17)(18)(19)(20)(21)(22). The key to the incision and drainage of parapelvic renal cysts via flexible ureteroscopy is the accurate location of the cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one patient with renal cell carcinoma and four patients with simple renal cysts also underwent relevant treatment for their respective conditions during the same surgery. (4) Compared with flexible ureteroscopy, there is no need to use a double J stent before and after surgery, and this reduces the cost of treatment 21 . Patient with ureteral stricture can also undergo this surgical approach.…”
Section: Discussionmentioning
confidence: 91%
“…The first RIR-HoLI series was reported by Li et al [16]. In their retrospective study, 13 (83%) of the 15 evaluable patients were asymptomatic at mean follow-up of 24.2 months (range 6–36 months).…”
Section: Discussionmentioning
confidence: 99%